Efficacy of LIFT for recurrent anal fistula. (25th April 2013) - Lehmann, J.‐P.; Graf, W.
Abstract Aim Ligation of the intersphincteric fistula tract (LIFT) is a novel sphincter‐preserving technique for anal fistula. This pilot study was designed to evaluate the results in patients with a recurrent fistula. Method Seventeen patients [nine men; median age 49 (range, 30–76) years] with a recurrent trans‐sphincteric fistula were treated with a LIFT procedure between June 2008 and February 2011. All were followed prospectively for a median of 16 (range, 5–27) weeks with clinical examination. Fifteen followed for 13.5 (range, 8–26) months by clinical examination also had three‐dimensional (3D) anal ultrasound. Results The duration of the procedure was 35 (range, 18–70) min. One patient developed a small local haematoma and one had a subcutaneous infection, but otherwise there was no morbidity. At follow up, 11 (65%) patients had a successful closure, two (12%) had a remaining sinus and four (23%) had a persistent fistula. The incidence of persistent or recurrent fistulae at 13.5 months was six (40%) of 15 patients. No de novo faecal incontinence was reported. Conclusion LIFT is a safe procedure for patients with recurrent anal fistula, with healing at short‐term and medium‐term follow‐up comparable with or superior to that of other sphincter‐preserving techniques. Larger studies with a longer follow up are needed to define the ultimate role of LIFT in patients with recurrence.